Magnetic Vortex Core in Cylindrical Nanostructures: Looking for Its Stability in Terms of Geometric and Magnetic Parameters - Altbir-Drullinsky, D; Escrig-Murua, J; Riveros-Rodriguez, A; Vidal-Silva, N (Elsevier B.V., 2016)
The relative stability of out-of-plane ferromagnetic, vortex without core and vortex with core configurations in cylindrical nanostructures are examined in terms of their geometric and magnetic parameters. Numerical calculations are done for general geometrical structures, while analytical expressions are obtained in the limiting cases of very long nanostructures. A magnetic phase diagram that clearly identifies the parameters required to obtain a vortex with core as minimum energy configuration is obtained by computing the transition lines between these configurations. The results define the geometric and magnetic parameters for which the vortex state can be made more stable by removing the highly energetic vortex core. Finally, a phase diagram that may be useful for the potencial use of vortices in technological applications is obtained and discussed. © 2015 Elsevier B.V.